Determinant Profitability of The Islamic Banking Industry inIndonesia: Literature Review - Danang Adi Putra; Amanda Alvi Nurdiantoro (Jurnal Akuntansi, 2024)
The growth of the Islamic banking industry in Indonesia can be attributed to the increasing public awareness of sharia principles in financial activities and strong government regulatory support, which includes regulations covering aspects ranging from capital requirement to operational procedures. it is evident that Shariah banks have the potential to thrive in the financial sector through strategic initiatives and a commitment to their core values. By leveraging technology and innovation, enhancing risk management practices, diversifying revenue streams, and strengthening governance and compliance processes, Shariah banks can position themselves for sustainable growth and success in the future. It is essential for Shariah banks to continue adapting to the changing landscape of the financial industry while staying true to their principles in order to maximize their profitability and impact.